Islamic literature: a Malaysian perspective - Baharudin, Nur Sheena; Altabaa, Homam (International Institute for Muslim Unity (IIMU), 2019)
The role of literature is, and has always been, influential and far-reaching. Although its importance may be of different degrees in different countries, the fact remains that literature continues to be one of the main factors that contribute to the makings of a culture. The need to re-introduce Islamic Literature as an accessible and structured study course is pivotal for many universities as they strive to enhance the dynamic role of their cultures on the global arena. This paper examines the need to re-introduce Islamic Literature not only as a body of literary works by Muslims from the past but as a body of literary works that is not restrictive in both time and space. Thus, contemporary students of literature have a rich classical heritage and contemporary output to examine. It is the contention of this article that the study of Islamic literature should have a wide geographical and historical scope that benefits from modern theories of literary criticism.